Junior High School Teachers’ Competence in Developing 2013 Curriculum Learning Materials - Ananda, Rusydi; Ritonga, Maharani Sartika; Daulay, Aidil Ridwan; Anggraini, Pauli; Abdi, Hasnan; Harahap, Addurun Nafis; Ritonga, Mashabi M. Noor (Universitas Pahlawan Tuanku Tambusai, 2023)
Due to technological advancements, educators must choose effective teaching materials that meet students' developmental needs. The purpose of this study is to evaluate teachers' capacity to create instructional materials for the 2013 curriculum at SMP IT Raudlatul Jannah Gayo Lues in Aceh. This study employs a qualitative methodology and a descriptive study design. Data gathering methods include observation, interviews, and documentation studies. After data analysis using data reduction techniques, conclusions are drawn by presenting the data. After passing a triangulation methodology test to ensure that the findings (research data) matched at least three different methods and data sources, the data was deemed genuine (informants). The study's findings revealed that: (1) the teacher's ability to plan a productive week by keeping track of the academic calendar; (2) the teacher's ability to put together an annual program (prota) in accordance with the curriculum and instructional materials; (3) the teacher's ability to set up semester programs in accordance with efficient study hours to meet the completion goals for each basic competency (KD) subject; and (4) the teacher's ability to create lesson plans (RPP). As a result, it was determined that the ability of the teachers at Raudlatul Jannah Gayo Lues Middle School to create learning resources was effective and good in accordance with the school's vision, mission, and goals.